Improving investment operations in commercial banks under the conditions of digital economy - Iuldasheva Barno Kuchkarovna; Axmedova Firuza Abdumadjitovna (THE INNOVATION ECONOMY, 2026)
the article presents the investment operations of commercial banks in our country’s digital economy, outlining the main objectives of these operations, as well as the existing challenges in their implementation. It also discusses the selection of optimal measures to address these problems and provides conclusions and proposals for improving the execution of these operations.